Heavy metals and ecological alterations resulting from wastewater discharge in Inner Puno Bay, Lake Titicaca - Maldonado, Ingrid (2023)
Wastewater continuously affects lacustrine ecosystems, such is the case of Lake Titicaca, the highest navigable lake in the world. To assess this impact, the concentration of heavy metals in water and sediment samples, physicochemical parameters, and the diversity of phytoplankton were evaluated in locations near the wastewater effluent. With the data on heavy metals in sediments, the Individual Potential Risk Factor Index (Eri) was assessed and the analysis of Potential Ecological Risk was conducted (PERI). The results revealed that pH, BOD5, NAMO and Phosphorus exceeded the limits established by Peruvian law. Additionally, we identified 14 metal elements in surface water samples; with a positive correlation between these metals and the sampling point (4), as well as total suspended solids (TSS). In the sediment samples, 35 different metal elements were detected. Specifically, point 4 showed the highest metal contamination levels, while point 9 exhibited the lowest levels. The Eri in sediments demonstrated that the concentration of cadmium (57.6) represents a moderate risk, while zinc represents the lowest risk (0.0); regarding the PERI, the sampling point closest to the discharge point (4) showed a moderate risk of contamination (113.48), and the point 9 represents the lowest value (14.68); reflecting that sewage affects water quality, negatively impacting phytoplankton diversity. Additionally, the As, Cu, Hg and Pb exceeded the limits set by regulations. Regarding phytoplankton diversity, generally low diversity values were recorded compared to other areas of the lake, with the species Oocystis sp. and Aulacoseira sp prevailing in most of the sampling points. Therefore, urgent measures are needed to remedy the situation in the Inner Puno Bay (IPB) of Lake Titicaca. © 2023 Elsevier B.V.